APPLICATION OF DEMONSTRATION METHODS AT THE SUBJECT OF MOTORBIKE ENGINE MAINTENANCE COMPETENCY IN EXPLAINING THE BASICS AND JOB STEPS IN ACCORDANCE WITH THE STANDARD OPERATING PROCEDURE REGARDING MAINTENANCE OF LUBRICANT SYSTEMS IN CLASS XI MOTORBIKE ENGI - Armada Suharsono (Jurusan Pendidikan Teknologi Dan Kejuruan, 2020)
This study aims: (1) How to apply the demonstration method in learning in the State Vocational School 1 Palangka Raya in class XI motorcycle engineering; (2) What are the results of the application of the demonstration method at SMK Negeri 1 Palangka Raya in class XI motorcycle engineering. This research is a descriptive study, with a population of whole students for first semester in class XI at SMK 1 Palangka Raya at academic year 2018/2019. The selected research sample is class XI TSM 1 for 39 students. The instruments used in this study are: teacher activity observation sheet, student activity observation sheet, student response questionnaire sheet, taken after implementing the demonstration method. By the results of this study, it can be concluded that the demonstration learning method on the subjects of Motorcycle Engine Maintenance Competency in explaining the basics and job steps in accordance with the standard operating procedure regarding the 80% treatment of the Lubricating System on cognitive aspects is satisfied. It is according to the criteria for achievement level in learning process at the range of 80% -100%.